Changing Income Inequality in OECD Countries: Updated Results from the Luxembourg Income Study (LIS) - Timothy M. Smeeding (Luxembourg Income Study (LIS), 2000)
The purpose of this study is to update the results first presented in 1995 in the OECD Monograph, 'Income Distribution in OECD Countries: Evidence from the Luxembourg Income Study' by Atkinson, Rainwater, and Smeeding (1995). Though only five years have passed since the publication of this volume, we are now able to compare the level of disposable income inequality across 20 nations, including Germany, in three separate periods using LIS. Moreover, we are now able to use several sets of national data to assess the changes in inequality that have taken place in recent years. The brief results are that the ranking of nations by the level of inequality at a point in time are more or less the same regardless of the year of comparison from roughly 1980-1997. But large changes in the distribution of income have taken place within many nations, with most finding a higher level of inequality in the mid-to-late 1990s than in the 1980s, and with Western Germany being no exception. Inequality, however, has not risen in Denmark or in Canada over this period, while its rise has slowed in several nations. This suggests that rising economic inequality is not inevitable. Strategies for improving these estimates are also discussed.
Keywords: 330; Einkommensverteilung; Vergleich; OECD-Staaten